Community Tourism Organization in the Parish Of Settlement, Cantón Riobamba - Priscila Carolina Montufar Zavala; Francisco Javier Chalen Moreano; María Yadira Cárdenas Moyano; María Guadalupe Escobar Murillo (Dominio de las Ciencias, 2024)
The research was conducted to understand why the Flores settlement has not developed community tourism, despite its significant natural and cultural attractions, such as the "Sisay Pacha" carnival, festivals, rituals, astronomy, and activities like green baskets. The settlement faces issues with poor organization of community tourism, underutilization of its heritage, and insufficient tourist services, limiting its growth. The study aims to identify the causes of this situation and propose solutions to strengthen community tourism. The research addresses the problem, the formulation of the problem, the justifications, the objectives, and the hypotheses. It presents a theoretical framework that includes background, theoretical bases, philosophical framework, and state of the art. It describes the methodology used, detailing the type and design of the research, the unit of analysis, the study population, the sample size and selection, the operationalization of variables, the consistency matrix, the research techniques and instruments, as well as the validity and reliability of these instruments, and the analysis and presentation of the information. It focuses on the results and discussion, covering the analysis, interpretation, hypothesis testing, conclusions, and recommendations. Finally, it presents the design of the Food and Beverage Production Management Process under the guidelines of the ISO 9001-2015 standard for the Flores parish. These findings reveal that the main obstacles to the development of community tourism in Flores are the lack of organization and training, poor destination promotion, deficient infrastructure, and limited tourist services. It is recommended to strengthen community organization, train local actors, promote the destination, improve infrastructure, and expand the range of services. The adoption of the ISO 9001-2015 standard is proposed to improve the quality of tourist services and the competitiveness of the destination.